Suggested: 3x/2-5y/3=-2 x/3+y/2=13/6 by substitution method - if (x+iy)^3=u+iv then show that u/x+v/y=4(x^2-y^2) - (xy^2+2x^2y^3)dx+(x^2y-x^3y^2)dy=0 - dy/dx=y^3+3x^2y/x^3+3xy^2 - 7x-3y=-12 and 2y=x+3 - x(x-1)dy/dx-(x-2)y=x^3(2x-1) - (d^2-4d+4)y=x^3 - x^2d^2y/dx^2-2x(1+x)dy/dx+2(1+x)y=x^3 - (d^4-2d^3+d^2)y=x^3 - draw the graph of the equation x-y+1=0 and 3x+2y-12=0 - test the consistency and solve 2x-y+3z=8 x-2y-z=-4 3x+y-4z=0 - 7x-15y=2 x+2y=3 by substitution method - solve by matrix method 2x+3y+3z=5x-2y+z=-4 3x-y-2z=3 - x/2+2y/3=-1 and x-y/3=3 - 2y=x+3 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.